Efektivitas Video Pengobatan TB Paru dalam Meningkatkan Pengetahuan Pendamping Minum Obat (PMO) dan Kepatuhan Pasien Minum Obat : Effectiveness of TB Treatment Video in Enhancing Knowledge of Medication Supervisors and Adherence to Medication in Patients - Daniati, Meisa; Romalina, Romalina (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2025)
Tuberculosis treatment takes 6-8 months to heal and complete treatment. Long-term treatment requires interaction from patients, such as compliance. Lack of communication and interaction between health workers and patients during the treatment process can lead to failure of compliance. Technology is needed to improve compliance with TB treatment; this has benefits for public health, such as reducing the rate of disease recurrence, drug resistance, and transmission of infection. Based on this, video education is needed to improve family knowledge and patient compliance in TB treatment. The study aimed to determine the effectiveness of TB treatment videos in improving the knowledge of PMO (Medication Companions) and compliance of pulmonary TB patients taking medication. The research method used was quasi-experimental (pre and post-test). The sample in this study were PMO and TB patients in Tanjungpinang City as many as 62 respondents. The instruments used were videos and questionnaires to measure PMO knowledge and patient compliance in taking medication. The results were an increase in the average knowledge in the intervention group compared to the control group and an increase in compliance from before being given therapy in both the control and intervention groups. TB treatment videos are effective in terms of knowledge of Treatment Companions (PMO) (p=0.000) and compliance of pulmonary TB patients in taking medication (p=0.002). TB treatment videos are expected to be used as PMO media to provide information to pulmonary TB patients.